Community Behavior on Social Media: The Existence of Gen Z in Fulfilling Islamic Religious Fear of Missing Out (FOMO) in Pagutan Indah - Helwa, Winda Azri (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
This study is motivated by the limited research on Islamic Religious Fear of Missing Out (FOMO) among Generation Z, despite its growing influence on digital religious engagement and identity construction in Indonesian Muslim communities. The study aims to analyze how Gen Z in Pagutan Indah behave on social media in fulfilling Islamic Religious FOMO, identify the psychological, social, and technological factors contributing to its emergence, and examine its influence on religious practices, social interaction patterns, and religious identity. Employing a qualitative design, the research involved 30 participants selected through purposive sampling. Data were collected through in-depth interviews, a focus group discussion, field observations, and digital artifact analysis, and examined using Braun and Clarke’s thematic analysis. The findings reveal that social media functions as a central arena for religious participation, where algorithmic exposure, peer norms, and emotional regulation collectively shape Islamic Religious FOMO. Gen Z’s engagement is characterized by hybrid religiosity, performative expressions of piety, and comparison-driven religious motivation, while internal spiritual needs, external social pressures, and technological reinforcement interact to intensify FOMO and influence both online behaviors and offline religious practices. These results support key propositions of the Theory of Planned Behavior, Digital Religion theory, the Mediatization of Religion framework, and the psychological model of FOMO, indicating that Islamic Religious FOMO plays a pivotal role in shaping contemporary youth religiosity. The implications highlight the need for enhanced digital literacy, reflective religious education, and community-based interventions, and point to the importance of future research on longitudinal patterns and broader regional contexts.